Mobility of oculomotor system and lability of visual analyzer in patients with primary open-angle glaucoma (Ukrainian Journal of Ophthalmology, 2026)
Purpose: to perform a comparative assessment of oculomotor system mobility and visual system lability in patients with primary open-angle glaucoma (POAG) of stages II and III with compensated IOP.Material and Methods: A total of 38 patients (38 eyes) with POAG were examined.  II stage was in 20 eyes and III stage was in 18 eyes. Oculomotor system mobility was studied according to impulse move frequency index, and visual system lability was assessed according to indices of critical flicker fusion and appearance frequency using an ophthalmic photomyostimulator unit (FMS-1). Results: Both in stage II and III of POAG, functional mobility of the oculomotor system was significantly lower as compared to the norm (р
Keywords: primary open-angle glaucoma; oculomotor system; visual system lability; ophthalmic photomyostimulator